2004
DOI: 10.1152/ajpheart.00222.2004
|View full text |Cite
|
Sign up to set email alerts
|

Neutral sphingomyelinase inhibitor scyphostatin prevents and ceramide mimics mechanotransduction in vascular endothelium

Abstract: Recently, we showed that neutral sphingomyelinase (N-SMase) is concentrated at the endothelial cell surface in caveolae and is activated to produce ceramide in an acute and transient manner by increase in flow rate and pressure in rat lung vasculature (Czarny M, Liu J, Oh P, and Schnitzer JE, J Biol Chem 278: 4424-4430, 2003). Here, we report further on our investigations of this new acute mechanotransduction pathway. We employed three experimental models to explore the role of N-SMase and ceramides in mechano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 49 publications
(65 reference statements)
2
51
0
2
Order By: Relevance
“…34 It has also been reported that sphingomyelin hydrolysis is activated on shear stress. 35 To examine the effect of shear stress on S1P synthesis and release by endothelial cells, we subjected MEECs to laminar shear stress. The p42/p44 extracellular signal-regulated kinase was rapidly phosphorylated when the endothelial cells were subjected to laminar shear stress (supplemental Figure IV).…”
Section: Shear Stress Induces S1p Release By Endothelial Cellsmentioning
confidence: 99%
“…34 It has also been reported that sphingomyelin hydrolysis is activated on shear stress. 35 To examine the effect of shear stress on S1P synthesis and release by endothelial cells, we subjected MEECs to laminar shear stress. The p42/p44 extracellular signal-regulated kinase was rapidly phosphorylated when the endothelial cells were subjected to laminar shear stress (supplemental Figure IV).…”
Section: Shear Stress Induces S1p Release By Endothelial Cellsmentioning
confidence: 99%
“…Caveolae have also been found to initiate TNFα-mediated apoptosis [224]. Neutral (but not acidic) sphingomyelinase activity is mechanically potentiated by increased vascular flow and could specifically be inhibited by a peptide that corresponds to the Cav1 CSD [223] or by scyphostatin, which specifically blocks neutral but not acid sphingomyelinase [225,226]. Cav1 interacts directly with PI3K that participates in the well-known phosphatidylinositol 3-kinase (PI3K)/Akt survival pathway, and its overexpression sensitizes fibroblasts to ceramide-induced death [227].…”
Section: Role Of Cav1 In Cell Death and Survivalmentioning
confidence: 99%
“…4 which demonstrate that the inhibition of endothelial NO formation by PAF is abrogated in isolated perfused lungs of mice deficient in ASM (Asm -/-). Once again the signaling events in endothelial cells of the systemic circulation are diametrically opposed to those in the lung, in that ceramide activates eNOS and stimulates endothelial NO formation in cultured bovine aortic endothelial cells (BAEC) [53,54], as well as in eNOS expressing chinese hamster ovary (CHO) cells [55,56]. Notably, the ceramide-induced stimulation of eNOS in systemic endothelial cells is independent of Ca 2+ -regulated pathways since it is unaffected by the intracellular Ca ] i signal [54], and likewise seems to be independent of the source of ceramide, as it is equally triggered by stimulation of both ASM and neutral sphingomyelinase (NSM) [57].…”
Section: Regulation Of Endothelial No Synthesis By Sphingomyelinase Amentioning
confidence: 99%